Tumor-derived extracellular vesicles and genitourinary cancers: from biological mechanisms to clinical applications - Wu, Xiaochui; Xu, Xiaoyuan; Du, Jiancheng; Mei, Jianfeng; Mao, Xiejuan; Lou, Kecheng (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundGenitourinary cancers, including prostate, bladder, and kidney cancers, represent significant global health burdens. Their early diagnosis and effective treatment continue to pose substantial clinical challenges. Traditional diagnostic methods often suffer from invasiveness or insufficient accuracy, whereas liquid biopsy technologies—particularly the analysis of tumor-derived extracellular vesicles (TDEVs)—offer transformative potential for non-invasive diagnosis and precision medicine.ObjectivesThis review comprehensively examines the biological functions, diagnostic utility, therapeutic potential, current challenges, and future directions of TDEVs in genitourinary cancers, aiming to bridge the gap between mechanistic understanding and clinical translation.MethodsA systematic literature search was conducted across PubMed, Embase, and Web of Science databases to collect studies published between 2018 and 2024 on TDEVs in prostate, bladder, and kidney cancers, with a focus on molecular mechanisms, clinical applications, and technological advances. Following PRISMA guidelines, we established predefined inclusion and exclusion criteria, conducted dual independent screening of search results, and performed quality assessment of included studies. A narrative review approach was employed to synthesize the evidence.Key FindingsTDEVs exhibit a dual nature in genitourinary cancers: they function as “architects” of tumor progression by remodeling the tumor microenvironment, inducing metastasis, and conferring therapeutic resistance, while simultaneously serving as “multifunctional allies” in cancer treatment. Clinically, TDEV-based liquid biopsy markers demonstrate superior performance compared to conventional detection methods, with engineered TDEVs emerging as promising platforms for targeted drug delivery and immunotherapy. However, significant challenges remain in standardization of isolation protocols, characterization methods, and efficient targeting strategies.ConclusionTDEVs represent a paradigm shift in precision oncology for genitourinary malignancies. With advancing technologies in isolation methods, multi-omics integration, and artificial intelligence applications, TDEVs are poised to become indispensable tools for early tumor detection, real-time monitoring, and personalized therapeutic strategies, heralding a new era in uro-oncological practice.